Implications of The Constitutional Court Decision No. 60/PUU-XXII/2024 on the Single Candidate Phenomenon in Regional Head Elections in Indonesia - Aji, Alan Bayu; Hesti Ayu Wahyuni (Jurnal Hukum In Concreto, 2025)
Simultaneous regional head elections in 2024 are a challenge for Indonesia's democratic system, especially with the phenomenon of single candidates even though the Constitutional Court has lowered the nomination threshold through Decision Number 60/PUU-XXII/2024. This study aims to analyze the impact of the Constitutional Court's decision on party political participation and identify factors that influence the sustainability of the single candidate phenomenon. This research uses a normative juridical method with a conceptual approach. The results show that although the lowering of the threshold has succeeded in increasing the opportunities for small parties to nominate candidates, the dominance of incumbents, high political costs, and weak political education remain significant obstacles so that there will still be single candidates in 37 Regions in the 2024 Simultaneous Regional Head Elections. Key findings suggest the need for additional arrangements, such as limiting the maximum party support for a single candidate, to encourage more participatory competition. This research confirms the importance of regulatory reform and political education to realize a more inclusive democracy in the context of regional head.